Keterampilan Berbicara Bahasa Jawa Ragam Krama Menggunakan Media Fun Learning Mat - ATIN, SRI -; Ikhwan, Afiful -; arif, zainal (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2021)
This study was conducted to describe the use of media fun learning mat in an effort to improve Javanese speaking skills, the variety of manners of fifth grade students is still low. Sources of data in this study were students of class V MI Muhammadiyah 10 Yanggong a total of 16 students. The data collection technique is done by interview, observation, test and documentation. The use of this media has a positive impact including; students are more active in learning activities, self-confidence increases, learning activities are more memorable and fun and students' oral test scores have increased with the percentage of classical completeness 87.50%. So it can be said that the use of fun learning mat media is able to improve the Javanese language speaking skills in a variety of manners, and is expected to be able to motivate students to practice it in everyday life.